A Systematic Review of the Effectiveness of Safewards: Has Enthusiasm Exceeded Evidence?. (17th February 2022) - Finch, Katie; Lawrence, Daniel; Williams, Marc O.; Thompson, Andrew R.; Hartwright, Christopher
Abstract: Safewards is intended to be an evidence-based approach to reduce levels of conflict and containment in mental health inpatient settings. A systematic review was carried out to examine whether Safewards is effective in reducing conflict and containment events; and improving ward climate. Searches for articles evaluating the implementation of Safewards was conducted using PsycINFO, PubMed, Web of Science, Cochrane Library and CINAHL. Thirteen studies were included for review after applying inclusion and exclusion criteria. The Quality Assessment Tool for Studies with Diverse Designs (QATSDD) was used to assess study quality and the majority of studies (N = 7) were rated as "moderate" quality. Whilst there is evidence to suggest that Safewards is effective for reducing conflict and containment in general mental health services, there is insufficient high-quality empirical evidence to support its effectiveness in settings beyond this. Further research using robust methodological designs with larger, more representative samples is required in order for the effectiveness of Safewards to be established across the range of contexts in which it is currently being applied.